Like a river glorious - Carson, Rae (Carson, Rae. Gold seer trilogy, 2017)
Lee Westfall escaped her murderous uncle and has found a new family in California, where Jefferson, her best friend, has started wooing her and their future seems bright. However, Hiram also survived, and when he kidnaps Lee, he will do anything to force her to use her talents for his own gain. What he doesn't know is that Lee has developed the power not only to hear the singing of gold, but to make it obey her call--a power she could use against him.